The structure of Bis(catecholato)silanes: phase adaptation by dynamic covalent chemistry of the Si-O bond - Hartmann, Deborah; Thorwart, Thaddäus; Müller, Rosa; Thusek, Jean; Schwabedissen, Jan; Mix, Andreas; Lamm, Jan-Hendrik; Neumann, Beate; Mitzel, Norbert W.; Greb, Lutz (Journal of the American Chemical Society, 2021)
Catechols occupy a unique role in the structural, bio-, and geochemistry of silicon. Although a wealth of knowledge exists on their hypercoordinate complexes, the structure of tetracoordinate bis(catecholato)silane, Si(catH)2 1, has been enigmatic since its first report in 1951. Indeed, the claim of a planar-tetracoordinated silicon in 1 triggered a prominent debate, which is unsettled to this day. Herewith, we present a comprehensive structural study on 1 and derivatives in the gas phase by electron diffraction, in a neon matrix by IR spectroscopy, in solution by diffusion NMR spectroscopy, and in the solid-state by X-ray diffraction and MAS NMR spectroscopy, complemented by high-level quantum-chemical computations. The compound exhibits unprecedented phase adaptation. In the gas phase, the monomeric bis(catecholato)silane is tetrahedral, but in the condensed phase, it is metastable toward oligomerization up to a degree controllable by the type of catechol, temperature, and concentration. For the first time, spectroscopic evidence is obtained for a rapid Si-O σ-bond metathesis reaction. Hence, this study sorts out a long-lasting debate and confirms dynamic covalent features for our Earth’s crust’s most abundant chemical bond.
Published: October 26, 2021
Gesehen am 05.10.2022